THE MENTAL DEVELOPMENT OF ISLAMIC RELIGION OF REHABILITATION INMATE IN THE PRISON - Prabowo, Yoga Sari (Sekolah Tinggi Agama Islam Muhammadiyah Tulungagung, 2019)
Mental religion development is a formation directed or aimed at one's mental (soul) towards that which is in accordance with religious teachings, which in this case is Islamic religion. So fostering Islamic religion is essentially the same as Islamic religious education, because what is meant by Islamic religious education is physical and spiritual guidance based on the laws of the teachings of Islamic religion to form the main personality according to the size of Islam. The role of religious education in forming a complete and noble human being is very important, therefore it is necessary to increase the implementation of religious education or mental development of religion in both the family, school, community and so on inmates. Because the majority of prisoners is detained is due to the low quality of their religious education. In order not to arise actions that violate the norms (religion, morality, etc.), it is necessary to live an Islamic soul in every human being so that it is expected to be able to reflect attitudes and behavior in accordance with his nature.